2009
DOI: 10.1177/1754073908097189
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Elicits the Social Sharing of Emotion: Theory and Empirical Review

Abstract: This review demonstrates that an individualist view of emotion and regulation is untenable. First, I question the plausibility of a developmental shift away from social interdependency in emotion regulation. Second, I show that there are multiple reasons for emotional experiences in adults to elicit a process of social sharing of emotion, and I review the supporting evidence. Third, I look at effects that emotion sharing entails at the interpersonal and at the collective levels. Fourth, I examine the contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
1,154
3
47

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,251 publications
(1,270 citation statements)
references
References 101 publications
66
1,154
3
47
Order By: Relevance
“…Thus, we hypothesized that sharing will predict positive emotion when the process of sharing alters how the sharer appraises the importance of the shared event. This hypothesis is consistent with findings that sharing negative events attenuates their emotional impact when sharing stimulates the cognitive work of modifying initial appraisals of the events (Rimé, 2009). …”
Section: How Social Sharing May Increase and Sustain Positive Emotionsupporting
confidence: 80%
“…Thus, we hypothesized that sharing will predict positive emotion when the process of sharing alters how the sharer appraises the importance of the shared event. This hypothesis is consistent with findings that sharing negative events attenuates their emotional impact when sharing stimulates the cognitive work of modifying initial appraisals of the events (Rimé, 2009). …”
Section: How Social Sharing May Increase and Sustain Positive Emotionsupporting
confidence: 80%
“…This is consistent with the hypothesis that positive emotions are more likely to be shared with weak contacts, while negative experiences are chosen to be shared through stronger ties. This result is in line with theories of social regulation of emotions [4] and with previous results in protest movements that showed that online negative emotions were associated with stronger collective action [30]. This appears also as a positive relationship between negative affect and tie strength in English, but is inconsistent with the absent pattern for Spanish, which points to the opposite direction but without consistent significance.…”
Section: Emotion and Social Tiessupporting
confidence: 45%
“…An explanation for this relationship comes from the theory of social sharing (Rimé, 2009;Rimé et al, 1992), which states that people want to communicate their emotions openly with others as a way to arouse empathy, to get help and support, to get social attention, or to strengthen social ties. Given the social character of WOM, it seems plausible to expect that experienced affect leads to WOM (Derbaix, 2003;Ladhari, 2007).…”
Section: The Influence Of Affect On Negative O-wommentioning
confidence: 99%
“…This paper intends to make three specific contributions to the existing body of literature. First, it adopts a sender-oriented perspective and uses the theory of social sharing (Rimé, 2009), self-perception theory (Bem, 1967) and cognitive dissonance theory (Festinger, 1957) to propose and empirically test interrelationships between emotions, negative O-WOM, and behavioral consequences. As such, we aim to develop more insight into the behavioral dynamics and consequences of negative O-WOM from a sender's perspective.…”
Section: Introductionmentioning
confidence: 99%